LB0003 Tocilizumab (TCZ) monotherapy is superior to adalimumab (ADA) monotherapy in reducing disease activity in patients with rheumatoid arthritis (RA): 24-week data from the phase 4 adacta trial. (23rd January 2014) - Gabay, C.; Emery, P.; van Vollenhoven, R.; Dikranian, A.; Alten, R.; Klearman, M.; Musselman, D.; Agarwal, S.; Green, J.; Kavanaugh, A.
Abstract : Background: Approximately 1/3 of RA patients (pts) on biologics receive them as monotherapy (without other DMARDs) [1, 2]. TCZ, an inhibitor of IL-6 receptor signalling, has been studied as monotherapy in 3 clinical trials [3–5], but direct comparison with an anti-TNF agent has not previously been performed. Objectives: To evaluate efficacy and safety of TCZ vs the anti-TNF agent ADA, both given as monotherapy, in RA pts with DAS28 >5.1. Methods: ADACTA was a multicentre, randomised, double-blind, 24-wk study designed specifically to test superiority in pts with RA of ≥6-mo duration who were MTX intolerant or for whom continued treatment with MTX was inappropriate. Pts were randomly assigned (1:1) to TCZ 8 mg/kg IV every 4 wks (+ placebo ADA) or ADA 40 mg subcutaneously (SC) every 2 wks (+ placebo TCZ) for 24 wks. Escape to wkly SC ADA/placebo was permitted at wk 16; 10 ADA and 7 TCZ pts escaped. The primary endpoint was mean change from baseline (BL) in DAS28 at 24 wks. Results: The intent-to-treat population included 325 pts (163 TCZ, 162 ADA). BL characteristics were similar between the TCZ and ADA arms: mean age 54.4 and 53.3 y, mean RA duration 7.3 and 6.3 y and mean DAS28 6.72 and 6.76, respectively. Efficacy at wk 24: mean change from BL in DAS28 was significantly greater with TCZ (–3.3) than with ADA (–1.8) (Table ). A numerical difference between the 2 arms in swollen and tender joint counts, ESR and patient global assessment in favour of TCZ was seen from wk 8 onward. Statistical significance was also achieved in favour of TCZ for DAS28 remission and low disease activity (LDA), and ACR20/50/70 responses (Table ). Safety: the incidence of adverse events (AEs) was similar between groups (TCZ: 82.1%; ADA: 82.7%). Serious AEs and serious infections also were similar (TCZ: 11.7%, 3.1%; ADA: 9.9%, 3.1%). Changes in laboratory values, including transaminase and LDL elevations and neutrophil reductions, occurred in both arms, with the proportion of pts with abnormal values higher in the TCZ arm. There were 2 deaths, both in the TCZ arm: 1 from sudden death, the other from reported illicit drug overdose. Conclusions: Monotherapy with TCZ was superior to monotherapy with ADA in reducing signs and symptoms of RA in MTX-intolerant pts or pts for whom MTX treatment was considered ineffective or inappropriate. The overall safety profile of both medications was consistent with previously reported data. References: Yazici, Bull NYU Hosp Jt Dis 2008;66:77. Soliman, Ann Rheum Dis 2011;70:583. Dougados Arthritis Rheum 2011 63(Suppl):S1032. Weinblatt Arthritis Rheum 2011 63(Suppl):S864. Jones Ann Rheum Dis 2010;69:88. Disclosure of Interest: C. Gabay Consultant for: Roche, Abbott, Merck, UCB, Pfizer, BMS, Merckserono, Novartis, Amgen, Speakers Bureau: Roche, Abbott, Merck, UCB, Pfizer, BMS, Merckserono, Novartis, Amgen, P. Emery Consultant for: Merck, Abbott, Pfizer, Roche, UCB, BMS, R. van Vollenhoven Grant/Research support from: Abbott, GSK, MSD, Pfizer, Roche, UCB, Consultant for: Abbott, GSK, MSD, Pfizer, Roche, UCB, A. Dikranian Speakers Bureau: Genentech, UCB, Abbott, BMS, R. Alten Grant/Research support from: BMS, Novartis, Pfizer, Roche, UCB, Consultant for: Abbott, BMS, Novartis, Pfizer, Roche, UCB, Speakers Bureau: Abbott, BMS, Novartis, Pfizer, Roche, UCB, M. Klearman Employee of: Genentech, a member of the Roche group, D. Musselman Employee of: Genentech, a member of the Roche group, S. Agarwal Shareholder of: Genentech, a member of the Roche group, Employee of: Genentech, a member of the Roche group, J. Green Shareholder of: Roche, Employee of: Roche, A. Kavanaugh Grant/Research support from: Roche, Amgen, Abbott, BMS, Janssen, UCB, Pfizer